An Analysis of the Effect of Content Marketing, Influencers, and Social Media on Consumer Purchase Decisions: A Case Study of Fashion Products Among TikTok Users - Sri Suwanti; Pitriyani Pitriyani; Usmala Dewi Siregar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of content marketing, influencers, and social media on consumer purchasing decisions for fashion products among TikTok users. The research employed a quantitative approach with a survey design and purposive sampling technique. Data were collected through questionnaires distributed to 96 TikTok users who had previously purchased fashion products online through the platform. Data analysis was conducted using multiple linear regression and significance testing at a 95% confidence level. The results indicate that content marketing has a positive and significant effect on purchasing decisions. Similarly, influencers and social media partially have a significant effect on consumer purchasing decisions. Simultaneously, the three independent variables significantly contribute to explaining the variation in purchasing decisions among TikTok fashion consumers. This study provides practical implications for fashion businesses to optimize content marketing strategies, collaborate with appropriate influencers, and strategically utilize social media features to enhance marketing effectiveness and increase sales conversion on digital platforms.